Cinnamomum burmannii Essential Oil as a Promising Antimicrobial Agent Against Cutaneous Pathogens: Mechanistic Insights into Its Anti-Malassezia furfur Activity - Wenwen Wang; Shuizhu Cai; Ying Wang; Yanhui Tan; Jing Xu; Ping Xiong (Microorganisms, 2025)
This study investigated the chemical composition, antibacterial activity and antifungal mechanisms of Cinnamomum burmannii essential oil (CBEO) obtained from leaves and branches through pilot-scale steam molecular distillation after D-borneol crystallization, focusing on its inhibitory effects against Malassezia furfur (M. furfur). GC-MS analysis identified 78 chemical constituents in CBEO, with the monoterpenoid D-borneol predominating. CBEO exhibited potent antifungal activity against M. furfur, with MIC and MFC values of 0.88 mg/mL and 1.75 mg/mL, respectively. Synergistic effects were observed when combined with ketoconazole (FICI = 0.5). At 2 × MIC concentration, CBEO suppressed 85.6% of biofilm formation (p < 0.01) as determined by crystal violet assay. SEM imaging revealed that CBEO treatment induced the formation of surface invaginations and pore structures on fungal cells. Quantitative detection of intracellular protein, nucleic acid, and ion leakage levels confirmed CBEO enhanced membrane permeability, resulting in cytoplasmic content leakage. Ergosterol binding assays confirmed cell membrane disruption (8-fold MIC increase), while UPLC quantification demonstrated dose-dependent suppression of ergosterol synthesis. Correspondingly, squalene epoxidase (SE) activity was significantly inhibited in treated cells. These findings systematically elucidate CBEO’s anti-M. furfur mechanisms, highlighting its potential as a natural antifungal agent for cosmeceutical applications.